The effect of external debt, foreign investment and exports on economic growth in 16 Asian countries - Syaparuddin, Syaparuddin; Pratama, Hajri Puja; Katamso, Katamso; Zevaya, Faradina (Universitas Muhammadiyah Yogyakarta, 2024)
This research aimed at analyzing the effect of economic growth lag, external debt, foreign investment and exports on economic growth in 16 Asian countries. The research used time series data from 2010-2020, and a sectional series in 16 Asian countries. The tool of analysis which was used in this research is Dynamic panel data regression. The result shows that the model of the system generalized method of the moment is the best model, the based on the result of analysis shows that economic growth lag has a positive significant influence, and in the short and long term the external debt has a negative significant influences, exports has positive significant influences on economic growth, while foreign investment does not have a significant influence towards economic growth.